Osteopontin is indispensible for AP1-mediated angiotensin II-related miR-21 transcription during cardiac fibrosis - Lorenzen, Johan M; Schauerte, Celina; Hübner, Anika; Kölling, Malte; Martino, Filippo; Scherf, Kristian; Batkai, Sandor; Zimmer, Karina; Foinquinos, Ariana; Kaucsar, Tamas; Fiedler, Jan; Kumarswamy, Regalla; et al. (European heart journal, 2015)
Osteopontin (OPN) is a multifunctional cytokine critically involved in cardiac fibrosis. However, the underlying mechanisms are unresolved. Non-coding RNAs are powerful regulators of gene expression and thus might mediate this process. OPN and miR-21 were significantly increased in cardiac biopsies of patients with myocardial fibrosis. Ang II infusion via osmotic minipumps led to specific miRNA regulations with miR-21 being strongly induced in wild-type (WT) but not OPN knockout (KO) mice. This was associated with enhanced cardiac collagen content, myofibroblast activation, ERK-MAP kinase as well as AKT signalling pathway activation and a reduced expression of Phosphatase and Tensin Homologue (PTEN) as well as SMAD7 in WT but not OPN KO mice. In contrast, cardiotropic AAV9-mediated overexpression of OPN in vivo further enhanced cardiac fibrosis. In vitro, Ang II induced expression of miR-21 in WT cardiac fibroblasts, while miR-21 levels were unchanged in OPN KO fibroblasts. As pri-miR-21 was also increased by Ang II, we studied potential involved upstream regulators; Electrophoretic Mobility Shift and Chromatin Immunoprecipitation analyses confirmed activation of the miR-21 upstream-transcription factor AP-1 by Ang II. Recombinant OPN directly activated miR-21, enhanced fibrosis, and activated the phosphoinositide 3-kinase pathway. Locked nucleic acid-mediated miR-21 silencing ameliorated cardiac fibrosis development in vivo. In cardiac fibrosis related to Ang II, miR-21 is transcriptionally activated and targets PTEN/SMAD7 resulting in increased fibroblast survival. OPN KO animals are protected from miR-21 increase and fibrosis development due to impaired AP-1 activation and fibroblast activation.